Workplace Stress and Employee Wellbeing: Case of Health Care Staff in UAE - Nasreen Khan; Sofia Khurshid (European Scientific Journal, ESJ, 2017)
Workplace stress is a world-wide concern and has been a subject of researchers, academicians, authorities and decision makers’ interest. It has evidently been considered to be causing poor performance, reduced employee morale, lack of autonomy, job insecurity and to greater extent the employee's wellbeing. Employees in healthcare and hospitality sector work in 24*7 work schedule due to the demanding nature of the industry. Empirical evidences have indicated that employee experience high stress on account of work overload and long working hours taking a toll on their mental and physical well-being. The purpose of this study was to investigate the impact of workplace stress on employee well-being among staff employees in the health care sector and hospitals in UAE. A total of 150 employees working at staff level in health care centers and hospitals in UAE were surveyed. The results showed that workplace has negative impact on employee well-being and the impact was found to be weak. The findings of the study suggest that an increase in workplace stresses will reduce wellbeing of employees. The researchers recommend that in order to reduce the impact of stress on employee well-being organizational support, family support and social support is essential.